The vulnerability of the pregnant woman in a conjugal situation in which there isan HIV/Aids serum difference - Azevedo, Anamaria F.; Guilhem, Dirce (Brazilian Journal of Sexually Transmitted Diseases, 2005)
Introduction: Gender inequality has become even more visible in the context of AIDS, especially for pregnant women. Matrimony, which can beseen as a stage for conflicts and negotiations, mirrors moral diversity, but can also be a support factor for coping with illness. Objective: To investi-gate the perceptions about living as an HIV serum different couple when the woman is pregnant. Methods: Qualitative research with seven couplesthrough open interviews. The results were obtained with the technique of content analysis, using a critical feminist bioethics perspective. Results: The women presented a disturbed life history and criticized the values and postures that their parents had. The conjugal relationship brings disappointment to them and the pregnancy is tense. The men had a difficult life due to poverty. They have to deal with the problem of accepting the wife’sillness and they feel insecure about the future of the relationship. They worry about the health of the baby and associate the woman’s role withmaternity. Conclusion: Conjugal vulnerability for pregnant women is a function of gender inequality, which characterizes the trajectories of inequality as well as the current situation in their lives. Cultural patterns such as romantic love, the ideal of maternity, and the wife’s acceptance of theman’s life project were present in the study. The pregnancy is marked by the fear of vertical transmission and by conjugal instability, even though italso contains a perspective for the future. The man oscillates between moral judgment and solidarity and the woman is afraid of abandonment. The diagnostic has an impact on the couple’s life and the profile of the couple contributes little toward coping with the disease.